The Influence of the Discipline of Online Assignment Collection Assisted by Edlink Sevima on the Learning Outcomes - Suswandari, Meidawati (Universitas Pendidikan Ganesha, 2021)
The interaction of students and lecturers is essential in learning. There is no face-to-face in class intensively the Covid-19 pandemic has an impact on student discipline in assignments. It has an impact on the low student learning outcomes. This study aims to analyze the collection of bold assignments assisted by Edlink Sevima on student learning outcomes. This research uses quantitative research. This research method is quantitative. The research sample was 42 students—data collection techniques were used in two ways: questionnaires and tests. The instrument used in collecting data is a questionnaire. Research test instruments include validity and reliability tests. Data analysis using statistical tests. The results showed that the rcount was 0.656, and in consultation with the Product Moment rtable, the significance level of 5% with N = 22 was 0.423. So it can be stated that rcount 0.656 > rtable 0.423 implies that the proposed hypothesis can be accepted. The implication of this research in learning is that it is essential to apply courageous task collection when studying. For students who have a high learning discipline attitude, the learning outcomes obtained are also high, namely learning outcomes. The results of the research state that there is an effect of collecting daring tasks assisted by Edlink Sevima on learning outcomes.